Management of school finance in Technical Secondary Schools: its implications for teaching and learning - Marzuki, S.; Ghani, M.F.A. (2008)
The purpose of this research is to find out the management of school finance in Technical Schools in Peninsular Malaysia and its implication towards the teaching - learning process. Some 43 technical secondary schools were involved in this study.